2019
DOI: 10.1136/bmjopen-2019-030626
|View full text |Cite
|
Sign up to set email alerts
|

Testing quality indicators and proposing benchmarks for physician-staffed emergency medical services: a prospective Nordic multicentre study

Abstract: ObjectivesA consensus study from 2017 developed 15 response-specific quality indicators (QIs) for physician-staffed emergency medical services (P-EMS). The aim of this study was to test these QIs for important characteristics in a real clinical setting. These characteristics were feasibility, rankability, variability, actionability and documentation. We further aimed to propose benchmarks for future quality measurements in P-EMS.DesignIn this prospective observational study, physician-staffed helicopter emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Over the years there have been minor revisions in the datasets, presented in Additional File 3. FHDB is used for daily reporting, scientific purposes and the governing of HEMS operations as a whole [16,[18][19][20]. The database also allows the creation of specific casereport forms for research projects or to monitor effects of specific quality improvement interventions.…”
Section: Finnhems Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Over the years there have been minor revisions in the datasets, presented in Additional File 3. FHDB is used for daily reporting, scientific purposes and the governing of HEMS operations as a whole [16,[18][19][20]. The database also allows the creation of specific casereport forms for research projects or to monitor effects of specific quality improvement interventions.…”
Section: Finnhems Databasementioning
confidence: 99%
“…The database contains only a subset of all EMS patients and dispatching criteria in our system might omit patient groups prominent in other systems. Despite these limitations, FHDB stores a large amount of nationwide data that can be, and already has been, used for further research in prehospital EMS and HEMS [16,18,19]. The data is being combined with the national discharge register and mortality data, enabling studies assessing survival, factors associated with changes in mortality and length of hospitalization.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…25 A good quality assessment system consists of multiple indicators addressing different dimensions of quality. Moreover, Haugland et al 18 recently suggested some characteristics essential for QIs in order to make them as useful in clinical practice as possible. Most of our developed indicators were process indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the indicators should be feasible, rankable, actionable, and variable. 17,18 By this, one understands that a QI, which is nonmeasurable, is of little value. The QI should also be possible to rank, from high to low or good to bad.…”
Section: Concept: Qismentioning
confidence: 99%
“…For the purpose of describing the quality of care for patients who died within 30 days, a quality scale for the EQUIPE quality indicators was used. This quality scale presents QI performances as average (within the interquartile range (IQR); yellow zone), above average (above IQR; green zone) or below average (below IQR; red zone) [16] based on the value of all QIs. Moreover, the quality scale defines a benchmark for every QI at the transition between the yellow and green zone.…”
Section: Methodsmentioning
confidence: 99%